2017
DOI: 10.1038/s41598-017-04102-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain metabolic connectivity at multiscale level in early Parkinson’s disease

Abstract: To explore the effects of PD pathology on brain connectivity, we characterized with an emergent computational approach the brain metabolic connectome using [18F]FDG-PET in early idiopathic PD patients. We applied whole-brain and pathology-based connectivity analyses, using sparse-inverse covariance estimation in thirty-four cognitively normal PD cases and thirty-four age-matched healthy subjects for comparisons. Further, we assessed high-order resting state networks by interregional correlation analysis. Whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 83 publications
9
57
0
Order By: Relevance
“…Thus, the most prominent network disruptions in our nondemented PD sample, of cortical sensorimotor systems as well as the cerebellum and thalamus, suggest that these disruptions reflect remote, downstream effects since synucleinopathy does not develop in these areas until late stages. This finding is consistent with previous PET blood flow and metabolism studies, which also suggest downstream consequences of neuropathology (Wooten et al 1982;Perlmutter and Raichle 1985;Eidelberg 1998;Hershey et al 1998;Sala et al 2017). In support of this idea, previous studies have demonstrated that proteinopathy may influence sensorimotor network function, suggesting that reduced FC arises as a downstream consequence of pathology in other regions.…”
Section: Pd Disrupts Network Downstream Of the Primary Sites Of Pathsupporting
confidence: 91%
“…Thus, the most prominent network disruptions in our nondemented PD sample, of cortical sensorimotor systems as well as the cerebellum and thalamus, suggest that these disruptions reflect remote, downstream effects since synucleinopathy does not develop in these areas until late stages. This finding is consistent with previous PET blood flow and metabolism studies, which also suggest downstream consequences of neuropathology (Wooten et al 1982;Perlmutter and Raichle 1985;Eidelberg 1998;Hershey et al 1998;Sala et al 2017). In support of this idea, previous studies have demonstrated that proteinopathy may influence sensorimotor network function, suggesting that reduced FC arises as a downstream consequence of pathology in other regions.…”
Section: Pd Disrupts Network Downstream Of the Primary Sites Of Pathsupporting
confidence: 91%
“…Building on the core principle that brain regions whose metabolism is correlated at rest are functionally interconnected (Horwitz, Duara, & Rapoport, ), we applied a voxelwise seed‐based interregional correlation analysis (Lee et al, ). This method was previously validated for [18F]FDG–PET data (Horwitz et al, ; Lee et al, ) and allows to derive resting‐state metabolic networks starting from proper seed regions (Ballarini et al, ; Iaccarino et al, ; Perani et al, ; Sala et al, ; Tomasi et al, ; see also Sala & Perani, for a recent review).…”
Section: Methodsmentioning
confidence: 99%
“…Once the destruction effect of moving MPs on tumor cells was demonstrated, the researchers focused their work on finding the most appropriate magnetic materials with larger mechanic torque of MPs under the variable magnetic field action. Thus, magnetite particles 6 , 7 , magnetic-vortex NiFe microdiscs prepared by magnetron sputtering followed by optical lithography 8 , 9 , ultrathin perpendicularly magnetized magnetic particles 10 , 11 , synthetic antiferromagnetic and ferrimagnetic microdiscs 12 with no magnetic remanence 13 , nanowires with various compositions obtained by electrodeposition in aluminum membranes 14 16 were studied at large for this purpose. The possibility of using STEM cells as carriers for the MPs to the tumor site, followed by the release of MPs based on magneto-mechanical actuation and destruction of cancer cells was also considered by the scientific world 17 .…”
Section: Introductionmentioning
confidence: 99%